2014
DOI: 10.1111/jvim.12406
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Treatment Outcomes of 41 Dogs with Sublingual Ectopic Thyroid Neoplasia

Abstract: BackgroundThyroid neoplasia is common in dogs, but there are few reports of dogs with ectopic, sublingual thyroid tumors.ObjectivesTo describe clinical features and outcomes of dogs with ectopic, sublingual thyroid neoplasia.AnimalsFive hundred and forty‐four dogs with thyroid neoplasia.MethodsThis retrospective study reviewed the medical records of dogs referred for thyroid neoplasia between 1995 and 2013. Data extracted included signalment, extent of thyroid disease (eutopic or ectopic; metastasis), serum th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 43 publications
0
39
0
4
Order By: Relevance
“…In einer weiteren Studie [7] wurden insgesamt 8 Hunde einer partiellen Zungenbeinresektion im Rahmen einer Tumorexzision unterzogen. In keinem dieser Fälle wurden postoperative Komplikationen dokumentiert.…”
Section: Orthotop Vs Ektotopunclassified
See 2 more Smart Citations
“…In einer weiteren Studie [7] wurden insgesamt 8 Hunde einer partiellen Zungenbeinresektion im Rahmen einer Tumorexzision unterzogen. In keinem dieser Fälle wurden postoperative Komplikationen dokumentiert.…”
Section: Orthotop Vs Ektotopunclassified
“…Das biologische Verhalten von Schilddrüsentumoren ist häufig aggressiv, mit einer Metastasierungsneigung in 25-80 % der betroffenen Hunde [1]. Eine Studie verglich die klinischen Eigenschaften von Hunden mit sublingualem ektopen Schilddrüsentumor und Hunden mit orthotopem Schilddrüsentumor [7]. Ektope Schilddrüsentumore zeigten dabei eine signifikant geringere Metastasierungsrate (15 % gegenüber 30 %) als orthotope Schilddrüsentumore.…”
Section: Metastasierung Und üBerlebenszeitunclassified
See 1 more Smart Citation
“…Die Szintigraphie bietet neben der Beurteilung der Anatomie und Aktivität der gesunden Schilddrüse die Möglichkeit, tumoröse Veränderungen zu diagnostizieren (1,8,9). Zudem ermöglicht sie den Nachweis von ektopem Schilddrüsengewebe sowie Metastasen eines Schilddrüsenkarzinoms und hilft bei der Suche nach postoperativ verbliebenem Schilddrüsengewebe (5,8,9,22). Eine quantitative Analyse des szintigraphischen Befunds kann durch Berechnung des Schilddrüsen-Speicheldrüsen-Quotienten (thyroid-to-salivary ratio) erfolgen (8).…”
Section: Diskussionunclassified
“…2,5 Reagan et al 6 and Campos et al 7 reported rates of lymph node metastasis at the time of definitive therapy of 7.1% and 15.7%, respectively, in dogs with thyroid carcinoma; however, methods of staging were not standardized. Broome et al 14 reported lymph node metastasis in 21.4% of their cohort dogs on the basis of thyroid scan data, although these dogs were not part of the main study population and were not reported to undergo any further diagnostic testing.…”
Section: Introductionmentioning
confidence: 99%